2022
DOI: 10.1097/md.0000000000031530
|View full text |Cite
|
Sign up to set email alerts
|

Elevated serum alkaline phosphatase correlates with postoperative cognitive dysfunction: A retrospective cohort study based on STROBE statement

Abstract: Little is known about the association between serum alkaline phosphatase (ALP) levels and postoperative cognitive dysfunction (POCD) after general anesthesia. Thus, we investigated the association of serum ALP levels with POCD in patients who underwent surgery with general anesthesia in a retrospective cohort study. We retrospectively collected data from patients who underwent surgery with general anesthesia between May 2016 and June 2020. Serum ALP activity was detected using a p-nitrophenyl phosphate assay. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Participants who had new‐onset VTE (DVT and/or PE) within 42 days after delivery were defined as VTE cases. Diagnoses of DVT and PE were described in our previous study detailly 8 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants who had new‐onset VTE (DVT and/or PE) within 42 days after delivery were defined as VTE cases. Diagnoses of DVT and PE were described in our previous study detailly 8 …”
Section: Methodsmentioning
confidence: 99%
“…3,4 Our and other studies have identified risk factors for VTE among pregnant women, including characteristics of the mothers (e.g., body mass index (BMI), age, multiple pregnancy), 5 and characteristics of obstetric (e.g., cesarean delivery, preterm delivery, preeclampsia), [5][6][7] and nutrition status of the mothers (e.g., serum alkaline phosphatase). 8 Abnormal blood pressure (BP) was also found to be related to inflammation and abnormal expression of the adhesion molecules, which may lead to VTE. 9,10 BP can be ameliorated with management, appropriate therapy, and/or lifestyle changes.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative cognitive dysfunction (POCD) refers to a common central nervous system complication after surgical anesthesia. 1 POCD is a common complication of central nervous system in elderly patients after surgery, which can occur days or even months after surgery. 2 POCD is characterized by difficulties in memory, concentration, personality, and information processing, seriously affecting patients' quality of life.…”
Section: Introductionmentioning
confidence: 99%